Implementation of CEFR in Malaysia: teachers’ awareness and the challenges - Nurul Farehah Mohamad Uri; Mohd Salehhuddin Abd Aziz (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study mainly seeks to investigate English teachers and Ministry of Education officials’ views on the implementation of CEFR in Malaysia. It also intends to explore the challenges encountered by the stakeholders in view of the adoption of CEFR onto Form 5 English syllabus and assessment. Data for this study were collected from questionnaires distributed to 331 English secondary school teachers and from in – depth interviews with two senior ministry officials. The findings revealed that most of the teachers had very limited knowledge, minimum exposure and low level of awareness about CEFR. Nevertheless, they were optimistic about the idea and believed that the framework is vital in order to improve the level of English proficiency of Malaysians. The officials in the ministry were also positive about the implementation plan despite the challenges and obstacles perceived. The teachers’ resistance, lack of training and negative conception that most teachers have namely it would be difficult to incorporate CEFR in their teaching are some of the main challenges identified in this study. In conclusion, the adoption of CEFR in Malaysia is seen as obligatory but sufficient time should be given by the ministry to ensure that all stakeholders are fully prepared and familiar with the framework before it is extensively introduced and used in the country.